Emotional Influence on Communication Effectiveness: A Study of Taylor’s University Students - Abu Seman, Shahri; Megat Ibrahim, Nan Zakiah; Mat Tahir, Hirnissa (Jurnal Evolusi, 2023)
This study investigates the profound relationship between emotions and their impact on communication. Emotions, expressed through cues like facial expressions, are central to daily interactions, influencing how individuals communicate and perceive others. The research distinguishes between primary, instinctive emotions (e.g., pleasure, frustration) felt similarly across cultures, and secondary emotions (e.g., love, guilt) that involve higher-order thinking, develop over time, and are often interpersonal. The core problem is that emotions frequently hinder communication, leading to discomfort and conflict. Recognizing and managing these emotional states is crucial for effective dialogue and resolving differences. This quantitative study aimed to determine the relationship between emotions and their impact on communication. Employing a survey design, data was collected from 140 students at Taylor’s University’s School of Media and Communication using stratified random sampling. Questionnaires adapted from Goleman (1995) and Millard J. Bienvenu (1971) measured emotions and communication impact, respectively. Results demonstrate a significant positive relationship between emotions and their impact on communication (r = .644, p < .000). This confirms that emotions strongly contribute to communication outcomes. The study emphasizes the critical role of emotional awareness for improved communication, fostering stronger social bonds, and enhancing both personal and professional interactions